Photodegradation of rhodamine B by Ag3PO4/Bi2MoO6nanocomposites under visible light illumination - Sudarat Sitthichai (2018)
© 2017 The Ceramic Society of Japan. All rights reserved. Heterostructure Ag3PO4/Bi2MoO6nanocomposites were synthesized by a depositionprecipitation method at high temperature and pressure. The as-synthesized products were characterized by X-ray diffraction, transmission electron microscopy and X-ray photoelectron spectroscopy. In this research, cubic Ag3PO4nanoparticles were deposited on orthorhombic Bi2MoO6nanoplates. For 10.0 wt% Ag3PO4loading, the Ag3PO4nanoparticles with 510nm in size were detected across the surface of Bi2MoO6nanoplates. The effect of Ag3PO4content on the photocatalytic properties was investigated by evaluating the degradation of rhodamine B under visible white light. The Ag3PO4/Bi2MoO6nanocomposites exhibited more enhanced photocatalytic activity than the pure Bi2MoO6. Electronhole diffusion in Ag3PO4/Bi2MoO6nanocomposites and photodegradation mechanism of rhodamine B were also discussed in this report.